Aptamer-based biosensor for prostate specific antigen detection using cobalt phthalocyanine-exfoliated graphite composites - Benise, Emihle (Rhodes University, Faculty of Science, Department of Chemistry)
The work focuses on the development of biosensors and their use for the detection of prostate specific antigen (PSA). Four cobalt phthalocyanines (CoPcs) complexes: (1) cobalt tetra pyridyloxy phthalocyanine, (2) cobalt tetra acetamidophenoxy phthalocyanine, (3) cobalt tris(acetamidophenoxy) mono benzoic acid phthalocyanine, and (4) cobalt tris(acetamidophenoxy) mono propionic acid phthalocyanine, an exfoliated graphite (EG), and aptamer are used to make probes for PSA detection. Each complex is Ï€-Ï€ stacked onto the EG to form EG-CoPc(Ï€-Ï€) hybrid which was used to modify a glassy carbon electrode (GCE). EG and CoPc were also used to modify the GCE sequential (seq) with CoPc on top to give GCE-EG-CoPc(seq). For the detection PSA, PSA specific aptamer was either sequential added or covalently linked to complexes 3 and 4 on the modified electrodes and was only sequentially added onto complexes 1 and 2 modified electrodes. Electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV) were the techniques used for the detection of PSA. The electrodes were found to be selective in bovine serum albumin, glucose and cysteine and stable when 50 DPV scans were run. Electrodes gave good % recovery when human serum was spiked with different PSA concentrations.
Keywords: Aptamer; Exfoliated graphite nano-platelets; Phthalocyanines; Impedance spectroscopy; Prostate-specific antigen